2019
DOI: 10.1055/s-0039-1700550
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Intestinal Epithelial Cell Turnover Correlates with Stimulated BMP Signaling Cascade following Intestinal Ischemia–Reperfusion in a Rat

Abstract: Introduction Bone morphogenetic proteins (BMPs) are a family of proteins that regulate proliferation and differentiation of intestinal epithelial cells. The purpose of this study was to evaluate the role of BMP signaling following intestinal ischemia–reperfusion (IR) in a rat model. Materials and Methods Male Sprague-Dawley rats were divided into four experimental groups: Sham-24 and Sham-48 rats underwent laparotomy and were sacrificed 24 or 48 hours later, respectively; IR-24 and IR-48 rats underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…While the absorptive Alpi + , Lgr5enterocytes move up toward the villus until they reach the villus tip where they go through apoptosis and shed themselves into the lumen to balance defensive barrier under different physiological conditions [43] (Figure 1). This process of turnover lasts for two to five days followed by a bone morphogenetic protein (BMP) sig naling pathway [44].…”
Section: Introduction Of Intestinal Epithelial Cell Polarity In Intes...mentioning
confidence: 99%
“…While the absorptive Alpi + , Lgr5enterocytes move up toward the villus until they reach the villus tip where they go through apoptosis and shed themselves into the lumen to balance defensive barrier under different physiological conditions [43] (Figure 1). This process of turnover lasts for two to five days followed by a bone morphogenetic protein (BMP) sig naling pathway [44].…”
Section: Introduction Of Intestinal Epithelial Cell Polarity In Intes...mentioning
confidence: 99%
“…Furthermore, several genes upregulated in M cells compared to Caco-2-cl1 cells were previously reported to play a role in the differentiation of IECs. Among these genes, BMP2 (bone morphogenetic protein 2) encodes a protein that promotes the differentiation of mature colonocytes [53] and is associated with increased epithelial cell turnover following intestinal ischemia-reperfusion in rats [54]. Similarly, an increased density of insulin-like growth factor 1 receptor, encoded by IGF1R gene, has been shown upon the differentiation of intestinal epithelial Caco-2 cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…These signaling pathways include Wnt/β-catenin, Hedgehog, Bone morphogenetic protein (BMP) and Notch [9]. Our research group has demonstrated that 24h following IR, Hedgehog [10] and BMP [11] signaling pathways were inhibited, which correlated with inhibited cell turnover. Signs of intestinal recovery appeared 48h after IR and were then correlated with activated Hedgehog and BMP signaling pathways.…”
Section: Academic Journal Of Pediatrics and Neonatologymentioning
confidence: 99%